Interaction of selected biomolecules and metabolites with amyloidogenic proteins - Kundu D.; Umesh; Dubey V.K. (My University, 2025)
The current manuscript reports docking and molecular interaction analyses of three FDA approved acetylcholinesterase inhibitors, nitrogenous bases and nucleotides with amyloidogenic proteins like hen egg white lysozyme (HEWL) and amyloid β peptide. After prediction of aggregation-prone regions in hen egg-white lysozyme and amyloid β peptide, grid boxes were defined for docking purposes covering these regions. We analyzed vital interactions and binding modes of molecules that dock near aggregation-prone regions of these proteins with acceptable statistics. The data hints toward the possibility that these molecules may bind to aggregation-prone regions and prevent amyloid/aggregation formation. We have also compared the binding energy and interactions of these molecules with certain other natural molecules viz. Curcumin, Coumarin and Resveratrol that have been previously reported to show anti-amyloidogenic activity as positive controls. Communicated by Ramaswamy H. Sarma. © 2020 Informa UK Limited, trading as Taylor & Francis Group.